Dehydroepiandrosterone sulfate stimulates expression of blood-testis-barrier proteins claudin-3 and -5 and tight junction formation via a Gna11-coupled receptor in Sertoli cells - Papadopoulos, Dimitrios; Dietze, Raimund; Shihan, Mazen; Kirch, Ulrike; Scheiner-Bobis, Georgios; Justus Liebig University Giessen (My University, 2016)
Dehydroepiandrosterone sulfate (DHEAS) is a circulating sulfated steroid considered to be a pro-androgen in mammalian physiology. Here we show that at a physiological concentration (1 µM), DHEAS induces the phosphorylation of the kinase Erk1/2 and of the transcription factors CREB and ATF-1 in the murine Sertoli cell line TM4. This signaling cascade stimulates the expression of the tight junction (TJ) proteins claudin-3 and claudin-5. As a consequence of the increased expression, tight junction connections between neighboring Sertoli cells are augmented, as demonstrated by measurements of transepithelial resistance. Phosphorylation of Erk1/2, CREB, or ATF-1 is not affected by the presence of the steroid sulfatase inhibitor STX64. Erk1/2 phosphorylation was not observed when dehydroepiandrosterone (DHEA) was used instead of DHEAS. Abrogation of androgen receptor (AR) expression by siRNA did not affect DHEAS-stimulated Erk1/2 phosphorylation, nor did it change DHEAS-induced stimulation of claudin-3 and claudin-5 expression. All of the above indicate that desulfation and conversion of DHEAS into a different steroid hormone is not required to trigger the DHEAS-induced signaling cascade. All activating effects of DHEAS, however, are abolished when the expression of the G-protein Gna11 is suppressed by siRNA, including claudin-3 and -5 expression and TJ formation between neighboring Sertoli cells as indicated by reduced transepithelial resistance. Taken together, these results are consistent with the effects of DHEAS being mediated through a membrane-bound G-protein-coupled receptor interacting with Gna11 in a signaling pathway that resembles the non-classical signaling pathways of steroid hormones. Considering the fact that DHEAS is produced in reproductive organs, these findings also suggest that DHEAS, by acting as an autonomous steroid hormone and influencing the formation and dynamics of the TJ at the blood-testis barrier, might play a crucial role for the regulation and maintenance of male fertility.
Keywords: ddc:610